Business mathematics - Abao, Zenon R.; Guhao Jr. ; Eugenio S. ;Maribbay, Jose B. ; Zorilla, Roland S. ; Mendoza, Violeta C. ; Mercado, Jesus P. ; Esller, Beda H. ; Partible, Fe G. ; Villa, Aurora E. (Mandaluyong City, 2008)
The book aims to provide a strong and firm foundation of the general principles and application of mathematics in different fields.
Keywords: Business mathematics